Faktor-Faktor Yang Mempengaruhi Degradasi Lingkungan di Indonesia - Nabila Fitri Alita; Yollit Permata Sari (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Abstract: This study aims to determine the effects of: (1) Industrialization (2) Gross Domestic Product percapita (3) forest area on ecological footprint in Indonesia. The data used in this research is time series data from 1992-2022. This research is quantitative research with the ECM (Error Correction Model) model. The observation results show that: (1) In the short term industrialization has a significant positive effect on environmental degradation in Indonesia. While Gross Domestic Product percapita and forest area have no significant effect on ecological footprint in Indonesia. (2) In the long-term industrialization has no significant effect on environmental degradation in Indonesia. While Gross Domestic Product percapita have a significant positive effect and forest area have a significant negative effect on ecological footprint in Indonesia. This study contributes to economic policy making, especially in improving environmental quality and formulating effective policies to reduce environmental damage in Indonesia. These findings are expected to be the basis for realizing sustainable development goals in Indonesia.